THE SYMBOL OF THE SEA IN JAMES FENIMORE COOPER’S NOVELS ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2026)
This thesis analyzes the artistic, philosophical and symbolic significance of the sea symbol in the works of the American writer James Fenimore Cooper. In particular, in the writer's novels on the theme of the sea, the sea is interpreted as a symbol expressing freedom, danger, the contradiction between man and nature, as well as the inner experiences of the heroes. During the research, the evolution of the image of the sea, its connection with the elements of romanticism and realism are studied on the example of such works as "The Pilot", "The Red Rover", "The Sea Lions". The dissertation is written on the basis of the literary-analytical method and reveals the place of the sea symbol in Cooper's work in American literature.